Biliary ileus. Peritonitis due to intestinal perforation due to diagnostic paracentesis
A patíent suffered from multiple biliary íleus; the obstructive gallstone was located in the íleum and two others in the second portian of duodenum. Perforation of a distended loop and consequent peritonitisi complicated diagnostica